The issue of the territorial self-governance in the Seym activity of the UNDA (Ukrainian National Democratic Alliance) at the beginning of 1930s - Zakharchyn, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The further realization of the reform of local self-governance and territorial organization of governance in Ukraine requires developments in a historical and legal aspect. Consequently, displaying the activity of Ukrainian political organizations in the interwar period regarding the issues of local and territorial self-governance is quite relevant. In the article, the position of the deputies of Ukrainian National Democratic Alliance (UNDA) in the parliament (seym) of the Second RzechPospolitaconcerning territorial and local self-governance is addressed. Despite the available researches, the issue of legislative activity of the representatives of the Ukrainian Club about the reformation of the bases of the territorial self-governance has not been reviewed. Ukrainian National Democratic Alliance as a part of united Ukrainian and Belarus electoral bloc entered the parliament of the Second RzechPospolita in autumn 1930. Between the other questions considered in the Seym, Ukrainian ambassadors didn’t neglect the issue of territorial and local self-governance. Particularly, within the consideration of the bill “About the partial change of the organization of territorial self-governance”, the Ukrainian deputies made statements about the electoral legislation in the prospective territorial units – collective gminas. There were some suggestions to hold the elections to the public councils based on five-adjective suffrage. This suffrage provided the elections of the public councils are supposed to be direct, equal, immediate, secret and proportial. In the discussion of the territorial self-governance much attention was paid to the imperfection of the main self-governance institutions. Changes proposed by the governors, in the opinion of Ukrainian ambassadors, didn’t give the representatives of the local communities the opportunity to get the positions in self-governance institutions. This was especially relevant in the Galychyna. The deputies connected the introduction of the law “About the partial change of the organization of territorial self-governance” with the international responsibilities of Poland regarding the granting of the autonomous status to the Eastern Galychyna. The project of changing the local self-government for the Ukrainian territory seemed worse than it was during the Austian-Hungarian governance. It introduced an ineffective collective gminas which didn’t meet the needs of time. In the article, one of the main tasks in the legislative activity of the Ukrainian ambassadors in the context of self-governance is highlighted – the protection of the rights of Ukrainians as a part of Poland.